Totally robotic isolated caudate‐lobe liver resection for hydatid disease: report of a case. Issue 2 (17th July 2015) - Di Benedetto, Fabrizio; Ballarin, Roberto; Tarantino, Giuseppe
Abstract: Background: Hepatic caudatectomy has always been considered a challenging procedure, because of the complex anatomy and deep location of this segment. Herein we report the first case of a totally robotic isolated caudate‐lobe liver resection ever performed for hydatid disease. Methods: A 55 year‐old man was referred to our institution after diagnosis was made of a 5.6 cm hepatic lesion of the caudate lobe. Radiological suspicion was for hydatid disease. The patient underwent robotic‐assisted hepatic caudatectomy. Results: The operative time was 280 min and the estimated blood loss was 200 ml. The postoperative course was uneventful. The drain was removed on post‐operative day 3 and the patient was discharged on post‐operative day 6. Conclusion: Robotic resection of the caudate lobe is a technically feasible procedure, which nevertheless requires high hepato‐pancreato‐biliary surgery skills, both in open an mini‐invasive approaches. It provides several technical advantages in the field of mini‐invasive surgery, yet assuring patient safety. Copyright © 2015 John Wiley & Sons, Ltd.